Design and performance of the level 1 calorimeter trigger for the BaBar detector - Dauncey, P; Andress, J; Adye, T; Chevalier, N; Claxton, B; Dyce, N; Foster, B; Galagedera, S; Kurup, A; Mass, A; McFall, J; McGrath, P; et al. (2000)
Since May 1999 the BaBar detector has been taking data at the PEP-II asymmetric electron-positron collider at the Stanford Linear Accelerator Center. California. This experiment requires a very large data sample and the PEP-II accelerator uses intense beams to deliver the high collision rates needed. This poses a severe challenge to the BaBar trigger system, which must reject the large rate of background signals resulting from the high beam currents whilst accepting the collisions of interest with very high efficiency. One of the systems that performs this task is the Level 1 Calorimeter Trigger, which identifies energy deposits left by particles in the BaBar calorimeter. It is a digital, custom, fixed latency system which makes heavy use of high-speed FPGA devices to allow flexibility in the choice of data filtering algorithms. Results from several intermediate processing stages are read out, allowing the selection algorithm to be fully analysed and optimized offline. In addition, the trigger is monitored in real time by sampling these data and cross-checking each stage of the trigger calculation against a software model. The design, implmentation, construction and performance of the Level 1 Calorimeter Trigger during the first year of BaBar operation are presented.